Efektivitas Pelatihan Relaksasi Otot Progresif terhadap Penurunan Kecemasan Primary Caregiver Anak Penderita Leukemia - Ananda Imanuela Nainggolan; Widyastuti Widyastuti; Ahmad Ridfah (Universitas Kristen Maranatha, 2020)
Anxiety level among primary caregivers in providing care for children with leukemia is classified as medium to high scale, so appropriate interventions are needed to overcome it. One appropriate intervention is progressive muscle relaxation techniques. This study aims to find out the effectiveness of progressive muscle relaxation training to reduce anxiety levels of primary caregiver children with leukemia. The method used in this study was a quasi experimental method with a nonrandomized pretest-posttest control group design with follow-up design. The subjects in this study were four people who were primary caregiver and the research instrument used was the Anxiety Scale. The subjects demostrated medium category on the anxiety scale. Further, the results showed that training in progressive muscle relaxation carried out routinely could reduce the anxiety of primary caregiver children with leukemia. Keywords: anxiety, primary caregiver, progressive muscle relaxation